Comparison of nasal douching with isotonic saline versus Ringer lactate in chronic rhinosinusitis: a randomized controlled trial - Paventhan, K.; R., Pradeep Krishna; C., Ramya Shree (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Nasal douching is a best effective and simple treatment procedure for chronic rhinosinusitis. This study compares the efficacy of nasal douching with isotonic saline solution versus ringer lactate solution in patients suffering from chronic rhinosinusitis. Methods: This randomized control trial was conducted among the patients with chronic rhinosinusitis who were attending the outpatient department of Otorhinolaryngology in Chettinad Hospital and Research Institute, Chennai, during the study period from June 2019 to December 2019. After randomization group A and B includes thirty cases of chronic rhinosinusitis each and they received nasal douching with saline and Ringer lactate two times a day for a period of three weeks and assessed using sino-nasal outcome test (SNOT) 20 during pre-treatment and post treatment. Data was entered in Microsoft excel and data analysis was done using SPSS version 17. Results: On assessing the overall SNOT 20 mean score, in both group A and group B, there was statistically significant improvement post treatment score when compare to pre-treatment scores. But the differences in improvement between the two groups were not found to be significant. Conclusions: Though isotonic saline and ringer lactate solution showed significant improvement after treatment both these are same with respect to efficacy in the treatment of douching for chronic rhinosinusitis with no difference in outcome.